هەڵوەشاندنەوەى کوردستانى عوسمانى لە ئەنجامى رێکەوتننامەى "سایکس-پیکۆ" دا 1916 - گه‌ڵاڵه‌یی, محمد احمد ابراهیم (Sulaimani Journal for Humanities, 2018)
Abstract In the nineteenth century, the Ottoman Kurdistan was a conflict zone amongst major powers, especially for Britain, France, Russia, Germany and Austria. However, the impact of these great powers in regard to their own benefits was a turning point in separating Ottoman Kurdistan from the Ottoman and Qajar empires, which lasted three hundred years. Then, the classical struggling among oriental empire came to an end. Especially after entering French forces into Ottoman areas, in the end of eighteenth century and Ottoman and Russian war from 1828 – 1829, which was the fresh start for separating Ottoman Kurdistan lands, until it reached 1877-1878 and World War I. Britain was supportive in developing Ottoman central power in the first half of nineteenth century, then ruining the Kurdish Ottoman empires. It also led Kurdish and Armenian tribes to start fighting against each other and then they let the major powers to enter the Ottoman Kurdistan areas especially the Russians, English and French. These struggles were resulted in recreating the future Ottoman Kurdistan, then remapping Middle East in the first quarter of the 20th century. Consequently, this had left a big impact on the Kurds destiny while making artificial regional states after Peace Conference and Treaty of Lausanne, which, of course, had an influence on Kurdistan’s political, social, economical, educational and cultural over the past century. This coincided with ruining Ottoman Kurdistan, which was one of the outcomes of Sykes-Picot Agreement between the Great Britain, Russian Empire and France.